Investigation of the Profiles of High School Students’ Mental Models of the Concept of Photoelectric Effects - Yeni Rima Liana (Scientiae Educatia: Jurnal Pendidikan Sains, 2020)
A mental model was students’ internal representation when they learned a concept. The conceptual model is a description of natural phenomena following the views of scientists. Most high school students have an idea of classical physics on understanding the concept of the photoelectric effects. Understanding the photoelectric effect is key to comprehend the fundamentals of quantum physics. The photoelectric effects can explain the quantization of energy that is explainable by a classical physics theory. This research's learning modeling aims to identify and investigate the profile of Class XII high school students’ mental models by regarding the concept of the photoelectric effects. This research employed descriptive methods. The research sample was selected purposively. This research used a diagnostic test for the pretest to determine the initial knowledge about the photoelectric effect of 30 students (12 male students and 18 female students) from the XII MIPA class at SMA Negeri 1 Pekalongan. The pretest questions consisted of 4 description questions. The pretest results were then analyzed and used to determine six students for an interview process, two students with high results, two students with medium results, and two students with low results. The interview results reveal that the students usually implement classical physics knowledge when developing mental models of the photoelectric effects.